Vulneración del derecho al trabajo en la Corte Provincial de Justicia de Loja - Ayala Andrade, Edison Fabricio (2023)
The set of constitutional rights and guarantees offered by the Constitution of the Republic of Ecuador, have a direct and broad application in labor activities that take place in the public and private sector, specifically in the Provincial Court of Justice of Loja, since it is labor rights that must be duly represented in the place where justice is administered. That, however, has not happened and contrary to this, this document reveals the violation of these rights, when the administration of the Council of the Judiciary has not implemented the principles of stability, promotions and incentives to all justice operators, leaving this conglomerate in the instability of their workplaces, despite spending years in their positions, adequately and efficiently complying with each of the procedures of the jurisdictional bodies. This investigation is focused on exposing the acts that, by action and omission, the Loja Judicial Council commits against its own administrators, ignoring constitutional and infra-constitutional principles and provisions. Through a dogmatic research method, with the proper collection of legal literature consistent with this topic, in the main research databases, it will be possible to deliver a result that reveals the apathy, negligence and violation of rights that the administration of this jurisdiction commits against its own officials, by not guaranteeing a process of contest of merits and opposition, disregarding the number of judicial servers without job security, and despite the years of honest, disciplined and efficient service.